Thermal load analysis and structure optimization of neutral beam injector cryosorption pump. Issue 1 (1st December 2022) - Liu, Xiaoxue; Tang, Ning; Cui, Zhiwei; Xie, Yuanlai
Abstract : In order to meet the high vacuum requirement of neutral beam source, cryosorption pump is used as the main pump, and the pumping performance of cryosorption pump depends on its cryogenic performance. To test and verify the feasibility of cryosorption pump steady running, modular design based on cryosorption pump, composed of 16 extraction unit in series, in a single suction unit as the research object, respectively for radiation and cryosorption pump baffle panel of the theory of heat load, and will result in finite element analysis software, the analysis of the temperature field of two structures, respectively and extraction unit structure optimization direction is put forward. The simulation results show that the normal operating temperature of the cryosorption pump can be reached under steady-state operating conditions, and the cryogenic performance of the extraction unit can be improved after the optimization of the structure, thus providing reference for the optimization of the cryogenic pump group.